AN UNFAIR SEMI-GREEDY REAL-TIME MULTIPROCESSOR SCHEDULING ALGORITHM. - ALHUSSIAN, HITHAM SEDDIG ALHASSAN (2014)
Optimal real-time multiprocessor scheduling algorithms always achieve higher processor utilization that is equal to the number of processors in the system. However, optimality always comes at the expense of scheduling overheads in terms of task preemptions and migrations which highly affect the practicability of the algorithm. This is because most of these algorithms achieve optimality by adhering to the fairness rule, in which tasks are forced to make progress in their executions at each time quanta or at the end of each time slice in a fluid schedule model; which corresponds to the deadlines of all tasks in the system. These preemptions and migrations add extra overheads that must be added to the worst case execution requirements of a task.